Proliferation of Postfeminist-Postmasculine Imagery & Disarticulation of Equality Activism: A Classroom of Feminist Media Studies as Politics of Emancipation - Noviani, Ratna (Jurnal Perempuan, 2016)
Since the end of 1990s, Indonesian media have been suddenly becoming feminists. It could be seen from the proliferation of images of what so-called â€œfemale individualismâ€. In this sense, women are depicted as being independent, success, beautiful and empowered. These images are followed by the rise of images of less superordinate and less powerful men than as previously required by patriarchal order. Subject-object relationship in terms of gender becomes fluid and interchangeable, as if the problem of inequality is already fixed and resolved. Such media images of postfeminism and postmasculinism are, in fact, disembedded and disconnected from the real problems of gender prevailed in the society. Those images tend to celebrate feminist success, but at the same time devaluing and negating feminist political activism. In this regard, integrating feminist perspectives into academic media studies in Indonesia becomes one of pivotal steps to challenge disarticulartion of feminism done via and by the media.